PENGARUH TRICHOKOMPOS DAN NPK ORGANIK TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN OKRA MERAH (Abelmochus esculentus L. Moench) PADA TANAH PMK - Muhammad Yogi Syahputra; Saripah Ulpah (DINAMIKA PERTANIAN, 2025)
This study aimed to determine the effect of the interaction between Trichocompost and Organic NPK on the growth and production of Red Okra (Abelmoschus esculentus L. Moench) in PMK soil. This research was conducted at the Faculty of Agriculture's experimental farm, Universitas Islam Riau, from January to April 2023. This study used a Completely Randomized Factorial Design with two factors. The first factor was Trichocompost with 4 treatment levels (0, 10, 20, and 30 g per plant), and the second factor was the dose of Organic NPK fertilizer with 4 treatment levels (0, 7.5, 15, and 22.5 g per plant). Each treatment consisted of 3 replications, for a total of 48 experimental units. Each experimental unit consisted of 4 plants; therefore, there were 192 plants. Two plants were used as samples for each experimental unit. Parameters observed were plant height, number of leaves, number of fruit per plant, number of fruit per plot, weight of fruit per plant, weight of fruit per plot, weight of fruit per fruit, and amount of remaining fruit. Observational data were analyzed statistically using the Follow-Up Test for Honest Significant Differences (BNJ) at the 5% level. The results showed that the interaction of Trichocompost and Organic NPK fertilizer had a significant effect on all observation parameters. The best treatment combination was found in Trichocompost 30 g/plant and Organic NPK fertilizer 22.5 g/plant.